“Efectos del etephon en maduración de frutos de vid (vitis labrusca) variedad borgoña negra, en San Martín-Perú” - Linares Garcia, Ramon (2003)
With the purpose of solving the problem of the maturation not uniform of the fruits of the grape the effect of the ethylene has been investigated (commercially well-known as Etephon) whose objectives consisted in the evaluation of the application of dose of Etephon in the uniform maturation, production of the grape (Vitis labrusca), variety black Borgoña Quarter note and to determine the relationship benefit - cost of each treatment. The experimental field was located in a vineyard of the neighborhood the Hill, sector "La Loma", District of San Antonio of Cumbaza, County and department San Martín in Perú, South Latitude 06º 25', Longitude West 76º 25' and Altitude 550 m.s.n.m. The design of blocks complete randomized was used with 3 repetitions and 7 treatments. With the doses of 3.5 and 2.5 l/ha you to uniformed the crop in 121 days and with color fruits delayed to Dark violet a Blackish violet whose relationship cost benefit was of 29.02 and 29.91 %; the doses of 3.5 and 4.5 l/ha with 6 731.00 and 6 069.00 Kg /ha. Also it was observed that when increasing the doses of Etephon it is increased the production costs among 21.12 % to 37.06%.